Preparing Future Health Professionals for Interprofessional Collaborative Practice Part 1: The Context for Learning - Portney, Leslie; Johnson, Alex F.; Knab, Mary (Seminars in Speech and Language, 2017)
The importance of interprofessional education and practice has been well documented for all health care disciplines. Our health care delivery system is challenged by the need to prepare health professions graduates with skills that get them ready to function as collaborative members of the health care team. Educators have long struggled to create interprofessional learning environments that would inculcate the needed values and competencies. The purpose of this article is to share one institution's path in developing an integrated context for learning across several disciplines to assure that graduates can fulfill their full professional roles in clinical care, education, advocacy, leadership, and quality improvement. Through a program called IMPACT Practice, the MGH Institute of Health Professions has developed an array of opportunities for students from different programs to interact with each other, emphasizing the collaborative skills that will benefit patients and clients as well as contribute to positive change within the health care system. These opportunities are based on core competencies developed by the Interprofessional Education Collaborative (IPEC) as well as institutional core competencies that go beyond IPEC to address the full professional role. In the second part of this article, the IMPACT experience will be described through the journey of one student in the Communication Sciences and Disorders program.
Keywords: Interprofessional education; interprofessional practice; core competencies